The parameters that play role in numerical parameter variation in two-center holographic recording in photorefractive lithium niobate (LiNbO3) and strontium barium niobate (SrxBa1-xNb2O6) - Demirbilek, Riza; Kilic, Mehmet (WILEY-V C H VERLAG GMBH, 2013)
We have conducted a numerical study of the dependence of nonvolatile data storage on the holographic parameter variation for a two-center holographic recording (TCHR) process. Parameters of the photorefractive crystals and the experimental conditions such as the electron mobility in the conduction band, the level concentrations, the electron-recombination coefficients, the bulk photovoltaic coefficient, the spatial period of modulation, the dielectric constant, and the modulation depth are studied numerically. The results of the numerical calculations showed that the significant parameters are the electron mobility in the conduction band, the electron-recombination coefficient, and the concentrations of the dopant levels (levels created due to the dopants) in the TCHR process. It seems that the electron-recombination coefficient for deep levels plays a more important role than the other parameters.
Keywords: holographic recording; lithium niobate; photorefractive crystals; strontium barium niobate; DOPED LINBO3; CRYSTALS; SENSITIVITY; DEPENDENCE; RU; Materials Science; Physics